2011
DOI: 10.1051/0004-6361/201116734
|View full text |Cite
|
Sign up to set email alerts
|

Testing the low-mass end of X-ray scaling relations with a sample ofChandragalaxy groups

Abstract: Context. Well-determined scaling relations between X-ray observables and cluster mass are essential for using large cluster samples to constrain fundamental cosmological parameters. Scaling relations between cluster masses and observables, such as the luminositytemperature, mass-temperature, luminosity-mass relations, have been investigated extensively, however the question of whether these relations hold true also for poor clusters and groups remains unsettled. Some evidence supports a "break" at the low end … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

42
183
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 130 publications
(231 citation statements)
references
References 113 publications
42
183
6
Order By: Relevance
“…We found that the median scaling factor of T ap and T 500 of the full sample, T ap /T 500 , was 1.2, where T 500 is the predicted temperature based on the L 500 − T 500 relation by Pratt et al (2009) using our value for L 500 . Eckmiller et al (2011) found that the slope of L X − T relation of galaxy groups (26 systems, L x ∼ 1−26 × 10 42 erg s −1 ) is slightly shallower than that derived for clusters (HIFLUGCS), but they are still consistent within the errors. These authors found no significant change either of the slope derived from a sample that combined groups and clusters to a sample consisting of clusters only, which is consistent with the results reported by Osmond & Ponman (2004).…”
Section: X -T Relation Of the Full Samplementioning
confidence: 60%
See 1 more Smart Citation
“…We found that the median scaling factor of T ap and T 500 of the full sample, T ap /T 500 , was 1.2, where T 500 is the predicted temperature based on the L 500 − T 500 relation by Pratt et al (2009) using our value for L 500 . Eckmiller et al (2011) found that the slope of L X − T relation of galaxy groups (26 systems, L x ∼ 1−26 × 10 42 erg s −1 ) is slightly shallower than that derived for clusters (HIFLUGCS), but they are still consistent within the errors. These authors found no significant change either of the slope derived from a sample that combined groups and clusters to a sample consisting of clusters only, which is consistent with the results reported by Osmond & Ponman (2004).…”
Section: X -T Relation Of the Full Samplementioning
confidence: 60%
“…Markevitch 1998;Pratt et al 2009;Mittal et al 2011;Eckmiller et al 2011;Reichert et al 2011;Takey et al 2011;Maughan et al 2012;Hilton et al 2012). These studies showed that the observed L X − T relation is much steeper than that predicted by self-similar evolution.…”
Section: Introductionmentioning
confidence: 80%
“…In the last few years deep X-ray surveys have provided the first statistically significant samples of X-ray galaxy groups (e.g. Finoguenov et al 2007;Gastaldello et al 2007;Sun et al 2009;Eckmiller et al 2011). For example Pratt et al (2009) examined possible causes for the observed steeper slopes, concluding that it is mostly associated with the variation of the gas content with mass, while structural variations play only a minor role.…”
Section: The L X − T and S − T Scaling Relationmentioning
confidence: 99%
“…The deviation of the L X − T relation from the pure gravitational prediction can also be interpreted in terms of entropy variation (Evrard & Henry 1991;Bower 1997;Tozzi & Norman 2001;Borgani et al 2001;Voit et al 2002;Younger & Bryan 2007;Eckmiller et al 2011). One way to inhibit the gas from reaching the center of the potential well, thus changing the gas fraction, is to increase the entropy of the gas.…”
Section: The L X − T and S − T Scaling Relationmentioning
confidence: 99%
See 1 more Smart Citation